Framework for alcohol policy in the WHO European Region. (World Health Organization, Regional Office for Europe, 2006)
The European Region is the WHO region with the highest alcohol intake in the world. Not only per capita consumption but also the disease burden from alcohol are twice the world average. Alcohol is the third-largest risk factor for death and disability in the Region and the largest risk factor among young people. The framework for alcohol policy in the Region, given in this booklet, is a timely response to the situation. It launches a new phase of alcohol policy, initiated and led by the WHO Regional Office for Europe. The framework aims to encourage and facilitate the development and implement.